2022
DOI: 10.1590/fst.45922
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cooking method and storage temperature on quality of three green vegetable semi-finished products

Abstract: Green vegetable semi-finished products (SFP) are deeply welcomed in daily life, but their quality will change during cooking and storage. This study investigated the effects of cooking method and storage temperature on quality of three green vegetable SFP. Fresh broccoli, green pepper and French bean were selected as research materials. They were blanched, microwaved and stir-fried to prepare the SFP, respectively. Then, the SFP were stored at 4 o C and 20 o C for seven days, respectively. The sensory score, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Guo et al (2023) reported that steaming increased the yellowish color of dried Flos Sophorae. Cooking methods had different effects on color or chlorophyll content due to energy transfer (Yang et al, 2022). The influence of drying processes on the pigments of sea lettuce was previously reported.…”
Section: Discussionmentioning
confidence: 90%
“…Guo et al (2023) reported that steaming increased the yellowish color of dried Flos Sophorae. Cooking methods had different effects on color or chlorophyll content due to energy transfer (Yang et al, 2022). The influence of drying processes on the pigments of sea lettuce was previously reported.…”
Section: Discussionmentioning
confidence: 90%